Nitrite content in meat products from the Serbian market and estimated intake. Issue 1 (October 2021) - Vranic, D; Koricanac, V; Milicevic, D; Djinovic-Stojanovic, J; Geric, T; Lilic, S; Petrovic, Z
Abstract: The aim of this study was to determine levels of nitrites in some meat products sold on the Serbian market over a period of 3 years (2018-2020) and to compare results with maximum residue levels as well to discuss dietary exposure of the Serbian adult population to nitrites.A total of 1291 meat product samples, produced by the Serbian meat industry or imported (509 dry fermented sausages, 37 semi-dry fermented sausages, 451 finely minced cooked sausages and 294 coarsely minced cooked sausages), were obtained from the Serbian retail market during 2018-2020.Higher mean levels of nitrite content, expressed as NaNO2, were found in cooked sausages (40.35 mg kg -1, finely minced and 33.75 mg kg -1, coarsely minced) compared to fermented sausages (1.86 mg kg -1 dry fermented and 1.83 mg kg -1, semi-dry fermented).The average dietary exposure to nitrites, expressed as nitrite ion, for the Serbian adult population varies from 0.001 to 0.015 mg kg -1 body weight (BW) day -1 and was far below the European acceptable daily intake (0.07 mg kg -1 BW day -1 ). In conclusion, the concentrations of nitrite in all meat products were below established maximum permitted levels (national and European), indicating that the use of nitrite as a food additive in Serbia is generally in line with existing regulations.